From pandemic to podium? Norwegian Olympic handball players’ journey to Tokyo 2020 - Aase, Eline; Abrahamsen, Frank Eirik; Gustafsson, Henrik (Frontiers in Psychology, 2025)
IntroductionMental preparation ahead of the Olympic Games (OGs) has been an area of interest for sports psychology researchers over several decades. However, there are few studies based on athlete perspectives of their experiences coping with pressure at this competition level. The COVID-19 pandemic also placed athletes in a demanding situation as they had to deal with the suspension of sport activity, isolation, and general uncertainty—culminating in the first postponement of the OGs in peacetime. Athletes had to balance coping with everyday life in a pandemic with navigating training in ever-changing conditions, indicating it was particularly valuable to investigate mental preparations ahead of the Tokyo OGs.ObjectiveThe current study aimed to explore how Norwegian handball players of various experience levels mentally prepared for the Tokyo OGs and how they experienced their preparations during the COVID-19 pandemic.MethodsRetrospective semi-structured interviews were conducted with seven handball players (four women, three men) who participated in the Tokyo OGs. A reflexive thematic analysis was completed to examine the findings.ResultsThe findings are described in two overarching themes: (1) failing to plan is planning to fail, and (2) balancing life and sports in a pandemic. Extensive preparations were done on an individual and team level. These incorporated mental, tactical, physical, and practical elements. Individual efforts varied and there were indications of certain team differences. The pandemic made the players’ everyday lives unpredictable, which was mentally exhausting for some. They coped with the uncertainties in different ways, though this often entailed focusing on the positive aspects. Overall, the players’ respective contexts affected their perceptions of the pandemic and the postponement of the OGs, and their appraisals of various stressors and subsequent coping strategies.ConclusionThe indications of team differences and variations in individual preparations imply that there was no “correct” way to prepare—all roads led to Tokyo. Experience was beneficial in several ways, including coping with the Olympic environment. Some found coping with the effects of the pandemic mentally exhausting, thus potentially affecting preparations. Still, the players got to practice dealing with unexpected events, which could aid future coping efforts.